2022
DOI: 10.3389/fvets.2022.1052553
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and anti-inflammatory effects of vitamin C on the liver of laying hens under chronic heat stress

Abstract: In this study, we investigated the therapeutic effect and mechanism of action of vitamin C on chronic heat stress (CHS)-induced liver oxidative damage and inflammation in laying hens. The thermoneutral control group (TN group) was kept at a constant temperature of 22 ± 1°C, while the chronic heat stress group (CHS group) and the vitamin C supplemented group (HSV group) were exposed to heat stress (HS) (36 ± 1°C, 8 h/d). The TN and HS groups were fed the basic diet at will, and the HSV group was supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In laying hens exposed to stress, egg production could be affected by the liver response which modulates the metabolism to maintain homeostasis [28]. In addition, the higher SD has been associated with increased mortality and disturbances, primarily due to heat stress, impacting the liver through oxidative stress and infammation [29][30][31]. Several studies have suggested that stress can be induced by densities lower than 465 cm 2 /hen, whereas in our study, the density was 450 cm 2 /hen in CC systems [25,32].…”
Section: Discussionmentioning
confidence: 99%
“…In laying hens exposed to stress, egg production could be affected by the liver response which modulates the metabolism to maintain homeostasis [28]. In addition, the higher SD has been associated with increased mortality and disturbances, primarily due to heat stress, impacting the liver through oxidative stress and infammation [29][30][31]. Several studies have suggested that stress can be induced by densities lower than 465 cm 2 /hen, whereas in our study, the density was 450 cm 2 /hen in CC systems [25,32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, vitamin C was reported to exert an anti-inflammatory effect in the liver against heat stress. (36) Since the mice in the present study were subjected to training, heat stress may play a major role in triggering liver inflammation. It has also been reported that dipeptides of L-glutamine and L-alanine exert antioxidant and antiinflammatory effects in the liver.…”
Section: Neurotrophic Factors and Serum Index Values After Admin-mentioning
confidence: 99%
“…Controlled environmental systems have reduced the incidence of acute heat stress in chickens, causing chronic heat stress to predominate. The optimal temperature range for poultry production is 19 to 22°C ( Du et al, 2022 ). Beyond this range, egg weight, eggshell weight, and eggshell thickness will all decrease significantly ( Mashaly et al, 2004 ).…”
Section: Treatments For Translucent Eggsmentioning
confidence: 99%
“…At 34°C, inflammatory responses in chickens increase, resulting in decreased egg production and feed intake, as well as intestinal morphology damage and subsequent intestinal health issues ( Deng et al, 2012 ). Heat stress is a primary source of oxidative stress, primarily affecting the liver ( Du et al, 2022 ). The main sources of calcium for eggshell formation are dietary calcium absorbed from the intestine and calcium released from the medullary bone.…”
Section: Treatments For Translucent Eggsmentioning
confidence: 99%